Idiopathic pulmonary fibrosis - problematic rare lung disease. Pathogenesis, diagnosis, treatment and prognosis - Aleksander Kłos; Justyna Szydłowska; Olga Żuchnik; Olgierd Król; Piotr Kwiatkowski; Beata Kuczyńska; Magdalena Czelej; Konrad Gładysz; Krzysztof Gieroba; Marcin Szydłowski (Kazimierz Wielki University, 2022)
Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal lung disease most often affecting people over the age of 50. Causes and pathogenesis of the disease are not fully understood. The non-specific symptoms of the disease prolongs diagnosis. It translates into a reduced chance of survival for patients. Treatment options for patients with IPF remain limited and sometimes lung transplantation is indicated. The prognosis of untreated IPF is 2 to 3 years. Aim of the study: Summary of current knowledge on the pathogenesis, diagnosis, treatment and prognosis of idiopathic pulmonary fibrosis (IPF). Methods and materials: A review of the literature available in the PubMed database, using the following  keywords:  "Idiopathic Pulmonary Fibrosis", "Idiopathic Pulmonary Fibrosis current treatment", "Idiopathic Pulmonary Fibrosis Pathogenesis". Results: The pathogenesis of IPF has been understood to some extent, but is still not described in detail. A chest CT scan and a lung biopsy are procedures that allow us to confidently diagnose IPF. We have two drugs at our disposal - pirfenidone and nintedanib, but their effect is not satisfactory. The prognosis of the disease is poor, and lung transplantation is the only way to improve it significantly. Conclusion: IPF is a severe lung disease in which the main problem is its difficult diagnosis and rapidly progressive course. We have drugs that delay the decline in lung function, but they do not improve the quality or prolong the life of the patient. It is also known that lung transplantation is the best solution, but it is rarely performed. The prognosis of the disease is poor, often worse than the prognosis of many cancers. It is possible that knowing the exact pathogenesis of the causes of the IPF would enable more effective treatment and diagnosis.